Knowledge and attitudes of parents of children with nursing bottle syndrome in Serdang, Malaysia - Syahrial, Dasrilsyah; Abdul Kadir, Rahimah; Yassin, Zaitun; Mohd Jali, Nazaruddin (Nihon University School of Dentistry, 1995)
A study was conducted to investigate the relationship between the parents' level of knowledge, and their attitudes to nursing bottle syndrome. Of 284 children aged 2-6 years clinically examined, 153 were diagnosed as having nursing bottle syndrome based on the criterion that at least one upper maxillary incisor was affected by caries. The parents of the 153 affected children were then interviewed by questionnaire. The findings suggested that parents had adequate knowledge and a positive attitude towards maintaining satisfactory dental care for their children. However, these attitudes were not reflected in the dental health of their children. The implications of these findings are discussed.